Porphyrin synthesis from ALA derivatives for photodynamic therapy. In vitro and in vivo studies - Perotti, C (Nature Publishing Group, 2004)
The aim of this work was to test in vitro and in vivo the efficacy of the derivatives of 5-aminolevulinic acid (ALA): hexyl-ALA (He-ALA), undecanoyl-ALA and R,S-2-(hydroximethyl)tetrahydropyranyl-ALA (THP-ALA) as pro-photosensitising agents. The compounds were assayed in a cell line derived from a murine mammary tumour, in tumour explants and after injection of the cells into mice. In vitro, undecanoyl-ALA and THP-ALA did not improve ALA efficacy in terms of porphyrin synthesis. On the other hand, half of the amount of ALA is required to obtain the same plateau amount of photosensitiser from He-ALA. However, this plateau value cannot be surpassed in spite of the four-times higher accumulation of ALA/He-ALA from the ALA derivative. This shows that He-ALA conversion to porphyrins but not He-ALA entry to the cells is limiting. Employing ionic exchange chromatography, we found that 80% of total uptake was He-ALA whereas only 20% was ALA. This suggests that the esterases, probably themselves regulated by the heme pathway, are limiting the conversion of ALA derivatives into porphyrins. A similar situation occurs with THP-ALA. Tumour explant porphyrin results correlate well with cell line data. However, i.p. injection of ALA derivatives to mice resulted in a lower porphyrin concentration in the tumour when compared to the administration of equimolar amounts of ALA, indicating that there should be retention of ALA derivatives either within the blood vessels in the initial phase of distribution and/or within the capillaries of the tumour.